PERANCANGAN SISTEM INFORMASI PEMETAAN FASILITAS KESEHATAN KOTA PADANG BERBASIS WEB DENGAN MEMANFAATKAN GOOGLE MAPS API - Zubair Shobrun Jamil; Dedy Irfan; Titi Sriwahyuni (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The development of information technology that very rapidly, have an impact transformation on various aspects of life. One of the growing information technology and widely implemented is a web-based information systems. Implementation of a web-based information system currently does not just present the information in text form, but also displays the information in the form of a map. In the terms of its utilization, application of GIS technology can be widely used in various fields, including in the health field. This can be used in the presentation of information dissemination of healthy facilities in the city of Padang. Information Systems for mapping Healthy Facilities in Padang City is a tool to convey information distribution healthy facilities that exist in Padang. This information system is designed with the PHP programming language and MySQL database as data storage. To display the digital maps, Google Maps is used because it has the APIs that can be integrated with multiple technologies. The presence of this information system is expected to provide facilities for those who need information about healthy facilities in Padang City. Keywords: Information System,Healthy Facilities, Google Maps, PHP, MySQL.